KEARIFAN LOKAL DAN RESILIENSI SOSIO-KULTURAL DALAM PENGELOLAAN HUTAN SAGU BERKELANJUTAN DI NEGERI IHAMAHU, KECAMATAN SAPARUA TIMUR, KABUPATEN MALUKU TENGAH - Yosafat Samuel Selanno; Marthina Tjoa; Maya M. S. Puttileihalat (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aimed to identify forms of local wisdom, analyze the level of socio-cultural resilience of the community, and examine the factors influencing sustainable sago forest management in Ihamahu Village, East Saparua District, Central Maluku Regency. The study employed a descriptive method with a mixed-methods approach. Data were collected through interviews with key informants and questionnaires administered to 30 respondents. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were analyzed using a Likert scale. The results revealed that the local wisdom practices still maintained by the community include customary rules for sago harvesting (pameri and letu), the role of the traditional institution Kewang, protection of natural sago regeneration, the Masohi tradition, and the transmission of traditional knowledge to younger generations. The level of socio-cultural resilience was categorized as very high, as reflected in the community's ability to preserve cultural values, adapt to technological advancements, and maintain customary institutions and social relationships. Supporting factors for sustainable sago forest management include strong customary laws, the active role of Kewang, the economic value of sago, and intergenerational knowledge transfer. Meanwhile, the main constraints include declining interest among younger generations, reduced mastery of traditional skills, and suboptimal management of sago waste. The findings indicate that local wisdom and socio-cultural resilience play a significant role in supporting the sustainability of sago forest management in Ihamahu Village.